Oxidative-Stress in Human Diseases (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Oxidative stress (OS) is recognized as a pivotal contributor to the pathogenesis of various, chronic human ailments, including cardiovascular and renal diseases, diabetes, neurodegenerative disorders, cancer, inflammatory conditions, and the aging process. It manifests as an imbalance between the generation and accumulation of reactive oxygen species (ROS) and reactive nitrogen species (RNS) within cells and tissues. OS occurs when the production of these species surpasses the detoxification capacity of the biological system. This compilation comprises cutting-edge research articles and reviews elucidating the interplay between OS and disease pathogenesis, as well as exploring the potential of natural antioxidants in mitigating such pathological conditions.